Social Networks in Education - Larionovs, Aleksandrs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Nowadays popularity of social networks (draugiem.lv, facebook etc.) is increasing, virtually every student has at least one account in one of the social networks. But the problem is that little is known about how to use social networking in Latvian education. The author of this paper will try to prevent it, to summarize available information on social networking in education.